Gujarātanuṃ nūra darabāra Śrī Gopāḷadāsa : Śrī Dattātraya Bāḷakrshṇa Kālelakaranī prastāvanā sāthe - Mahetā, Kalyāṇajī Viṭhṭhalajī, b. 1890 (SAMP early 20th-century Indian books project, 1923)
Biography of Gopāladāsa Desāī, 1871-1951, political scientist from Saurashtra.